Lunar polar rover science operations: Lessons learned and mission architecture implications derived from the Mojave Volatiles Prospector (MVP) terrestrial field campaign. Issue 4 (15th August 2016) - Heldmann, Jennifer L.; Colaprete, Anthony; Elphic, Richard C.; Lim, Darlene; Deans, Matthew; Cook, Amanda; Roush, Ted; Skok, J.R.; Button, Nicole E.; Karunatillake, S.; Stoker, Carol; Marquez, Jessica J.; et al.
Highlights: The distribution and characteristics of lunar polar volatiles are mostly unknown. A lunar rover mission is required to map the spatial distribution of polar volatiles. A new concept of operations is required for a short duration lunar rover mission. Field testing yields insights into science and operations for a future Moon mission. Abstract: The Mojave Volatiles Prospector (MVP) project is a science-driven field program with the goal of producing critical knowledge for conducting robotic exploration of the Moon. Specifically, MVP focuses on studying a lunar mission analog to characterize the form and distribution of lunar volatiles. Although lunar volatiles are known to be present near the poles of the Moon, the three dimensional distribution and physical characteristics of lunar polar volatiles are largely unknown. A landed mission with the ability to traverse the lunar surface is thus required to characterize the spatial distribution of lunar polar volatiles. NASA's Resource Prospector (RP) mission is a lunar polar rover mission that will operate primarily in sunlit regions near a lunar pole with near-real time operations to characterize the vertical and horizontal distribution of volatiles. The MVP project was conducted as a field campaign relevant to the RP lunar mission to provide science, payload, and operational lessons learned to the development of a real-time, short-duration lunar polar volatiles prospecting mission. To achieve these goals, the MVP project conducted a simulated lunar rover mission to investigate the composition and distribution of surface and subsurface volatiles in a natural environment with an unknown volatile distribution within the Mojave Desert, improving our understanding of how to find, characterize, and access volatiles on the Moon.